Design, Fabrication, and Accuracy of a Novel Noncovering Lock-Mechanism Bilateral Patient-Specific Drill Guide Template for Nondeformed and Deformed Thoracic Spines. Issue 2 (July 2021) - Ashouri-Sanjani, Mehran; Mohammadi-Moghadam, Shima; Azimi, Parisa; Arjmand, Navid
Background : Pedicle screw (PS) placement has been widely used in fusion surgeries on the thoracic spine. Achieving cost-effective yet accurate placements through nonradiation techniques remains challenging. Questions/Purposes : Novel noncovering lock-mechanism bilateral vertebra-specific drill guides for PS placement were designed/fabricated, and their accuracy for both nondeformed and deformed thoracic spines was tested. Methods : One nondeformed and 1 severe scoliosis human thoracic spine underwent computed tomographic (CT) scanning, and 2 identical proportions of each were 3-dimensional (3D) printed. Pedicle-specific optimal (no perforation) drilling trajectories were determined on the CT images based on the entry point/orientation/diameter/length of each PS. Vertebra-specific templates were designed and 3D printed, assuring minimal yet firm contacts with the vertebrae through a noncovering lock mechanism. One model of each patient was drilled using the freehand and one using the template guides (96 pedicle drillings). Postoperative CT scans from the models with the inserted PSs were obtained and superimposed on the preoperative planned models to evaluate deviations of the PSs. Results : All templates fitted their corresponding vertebra during the simulated operations. As compared with the freehand approach, PS placement deviations from their preplanned positions were significantly reduced: for the nonscoliosis model, from 2.4 to 0.9 mm for the entry point, 5.0° to 3.3° for the transverse plane angle, 7.1° to 2.2° for the sagittal plane angle, and 8.5° to 4.1° for the 3D angle, improving the success rate from 71.7% to 93.5%. Conclusions : These guides are valuable, as the accurate PS trajectory could be customized preoperatively to match the patients' unique anatomy. In vivo studies will be required to validate this approach.